Застосування кімнатних рекуператорів для вентилювання шкільних приміщень - Юркевич, Ю. С.; Возняк, О. Т.; Савченко, О. О.; Гулай, Б. І.; Yurkevych, Yu.; Voznyak, O.; Savchenko, O.; Gulay, B. (Видавництво Львівської політехніки, 2019)
Підтримання належних параметрів мікроклімату в класних кімнатах та аудиторіях, які б забезпечували добре самопочуття учнів, є важливим соціальним завданням, оскільки в навчальних закладах молодь проводить значну частину свого часу. Висока концентрація СО2 у приміщеннях класів погіршує самопочуття та знижує працездатність учнів, а також спричиняє недостатнє засвоєння ними навчального матеріалу. Встановлено, що лише механічна припливно-витяжна вентиляція з нормою повітрообміну 30 м3/год на особу забезпечує належні санітарно-гігієнічні умови в приміщеннях класів. Проте в існуючих шкільних спорудах забезпечити такий повітрообмін завдяки централізованим системам вентиляції складно через існуючі архітектурно-будівельні вирішення. Тому в таких об’єктах доцільно застосовувати кімнатні припливно-витяжні рекуператори, причому для досягнення потрібного повітрообміну в класній кімнаті слід встановити від 2 до 7 таких агрегатів. Таку кількість рекуператорів в більшості класних приміщень можна змонтувати лише дещо нижче рівня підвіконника, через що припливне повітря буде подаватися безпосередньо на людину. У зв’язку з цим необхідно перевірити параметри мікроклімату на робочому місці, зокрема рухомість та температуру припливного повітря. Доцільно також встановити аналітичні розрахункові залежності та на їх основі побудувати номограми для інженерних розрахунків.

Maintaining the proper parameters of the microclimate in classrooms and classrooms to ensure the well-being of students is an important social task, since young people spend a significant part of their time in educational institutions. Failure to admit microclimate parameters in class rooms, in particular due to the high concentration of CO2, leads to deterioration of the state of health and disability of the students, as well as to the inadequate absorption of the training material. It was established that only mechanical ventilation with an air exchange rate of 30 m3/year per person provides proper sanitary and hygienic conditions in the premises of classes. However, in existing school facilities, it is difficult to provide such air exchange due to centralized inflow and exhaust ventilation systems due to already existing architectural and construction decisions. Therefore, in such objects, it is advisable to use inflow-exhaust room recuperators, but most of them are oriented on residential and office premises with a small number of people (2–3 persons) and have insufficient productivity. Unlike them, company Prana manufactures a range of recuperators with an efficiency of inflow air from 115 to 650 m3/h. Depending on the chosen model of the recuperator Prana, to achieve the desired air exchange, in the classroom should be set from 2 to 7 such aggregates. Such a number of Prana recuperators in most classrooms can be mounted only slightly below the level of the window sill, through which the flow of air will be fed directly to a person. In connection with this, it is necessary to check the parameters of the microclimate in the workplace, in particular velocity and temperature of the inflow air, as well as determine the coefficients of attenuation of the velocity m and the temperature n of the air stream coming from the recuperator Prana. It is also advisable to establish analytical settlement dependencies and create charts for engineering calculations based on them.
Application of room recuperators for ventilation of school apartments
Keywords: діоксид вуглецю; приміщення класу; повітрообмін; механічна система вентиляції; оптимальні параметри мікроклімату; рекуператор; carbon dioxide; classroom; air exchange; mechanical ventilation system; optimal microclimate parameters; recuperator; 628.8